DYNAMICS OF DEMOCRACY AND AUTHORITARIANISM IN INDONESIA: A CRITICISM OF THE SOCIO-POLITICAL INTERPRETATION OF SYU’BAH ASA IN THE NEW ORDER ERA - Hidayatullah, Adi Rahmat (Universitas Nurul Jadid, 2024)
This article analyzes the socio-political interpretation of Syu’bah Asa’s work entitled “Dalam Cahaya Al-Qur’an: Tafsir Ayat-Ayat Sosial dan Politik” as a response to the authoritarianism of the New Order regime in Indonesia. With a linguistic and thematic approach, this study explores how Syu’bah uses the Qur’an to criticize justice issues, human rights violations, corruption, and pseudo-diversity. This interpretation not only offers moral solutions; the interpreter also intends to build religious and social awareness in society by using the texts of the Qur’an to reflect socio-political realities, fight for democracy, and even reflect the spirit of resistance against the practice of repressive power domination. Through contextual interpretation, Syu’bah Asa links the verses of the Qur’an with the socio-political realities of that time, such as discriminatory policies against certain groups and the silencing of civil liberties. There are at least two important findings in this paper namely: First, Syu’bah Asa conveys criticism of the repressive policies of the New Order through an interpretation of verses that highlight the issues of justice, human rights violations, corruption, and pseudo-diversity. Second, the interpretation is not only a reflection of social conditions but also offers democracy as a system based on religious morality. In conclusion, by reflecting on the verses of the Qur’an, Syu’bah Asa wants to remind and emphasize the relevance of the Qur’an in building critical socio-political awareness and inviting civil society and the authorities (government) to continue to introspect and improve themselves, especially government officials in carrying out the mandate of the people and the Almighty God